Development and implementation of healthcare technologies in the structural-functional model of public administration: bronchopulmonal dysplasia experience - Demikhov, Oleksii; Dehtyarova, Iya; Tkachenko, Nataliia; Torianyk, Inna; Kroitor, Volodymyr (Bangladesh Journal of Medical Science, 2022)
The results obtained in the previous research and the author’s analysis of the ways and experience of solving similar organizational and methodological problems have identified the need for structural and logical systematization and their generalization for the sound development of structural-functional model (SFM) medical care for children 0-3 years old with bronchopulmonal dysplasia (BPD) and children of older age groups dysplastic dependent pathology of broncho-pulmonal system. The urgency of such development is conditioned by the existing socio-medical significance of the problem of health preservation, first of all prematurely born children with low and low body weight, high levels of their disability and morbidity. The aim of the study: to substantiate and develop a systematic complex of regulatory and legal support for SFM of medical care for children with BPD and dysplastic-dependent pathology of the bronchopulmonary system, in particular with regard to the introduction of health-improving measures. The author provides the legal and legal support for the components of the SFM assistance to children with BPD and dysplastic dependent pathology of broncho-pulmonal system, in particular regarding the improvement of health technologies in regional health systems. In order to improve this area of legislative and regulatory support, in 2014-2016 the directions of implementation of the legislative initiative were determined. The substantiated, submitted for consideration seven legislative acts of Ukraine, which improved the regulatory and legal support of the SFM components. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 361-367